2021
DOI: 10.1093/icvts/ivab209
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants and facility type impact adherence to best practices in operable IIIAN2 lung cancer

Abstract: OBJECTIVES We aimed to identify patient- and facility-specific predictors of collective adherence to 4 recommended best treatment practices in operable IIIAN2 non-small-cell lung cancer (NSCLC) and test the hypothesis that collective adherence is associated with superior survival. METHODS We queried the National Cancer Database for clinical stage IIIAN2 NSCLC patients undergoing surgery during 2010–2015. The following best pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…Moreover, most observed comorbidities were chronic and being treated. Occupational skill level did not significantly affect the likelihood of receiving guideline adherent treatment, in contrast to an earlier report, which found that lower educational level and residence in a rural county were associated with a lack of adherence to guidelines in patients with stage III NSCLC [23]. In our study population, only 9.0% of the NSCLC patients had a high occupational level, a much lower percentage than in the general population of Ostrobothnia [24].…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, most observed comorbidities were chronic and being treated. Occupational skill level did not significantly affect the likelihood of receiving guideline adherent treatment, in contrast to an earlier report, which found that lower educational level and residence in a rural county were associated with a lack of adherence to guidelines in patients with stage III NSCLC [23]. In our study population, only 9.0% of the NSCLC patients had a high occupational level, a much lower percentage than in the general population of Ostrobothnia [24].…”
Section: Discussioncontrasting
confidence: 99%
“…Academic centers had higher rates of performing neck dissection. This is consistent with previous studies that have shown that academic centers may more often provide guideline-concordant treatment for patients, [24][25][26][27] potentially due to a variety of factors including better access to resources such as highly specialized providers, and differences in patient preferences and tumor presentations at academic and community facilities. This may be particularly important when considering that certain populations of patients may have limited access to academic medical centers.…”
Section: Discussionsupporting
confidence: 91%
“… 17 , 19 This finding is unexpected and interesting given that academic centers are widely reported to have superior survival outcomes in NSCLC by virtue of being more guideline concordant than other center types. 1 , 24 This suggests that achieving better outcomes in this group of patients is an exceedingly complex and multifactorial process and one that clearly needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Social determinants of health impact treatment quality and survival in patients with non–small cell lung cancer (NSCLC). 1 , 2 Safety-net hospitals have previously been grouped with other proposed patient- and facility-specific contributors of these healthcare disparities. 3 The Institute of Medicine defines safety-net hospitals as “those providers that organize and deliver a significant level of health care and other related services to uninsured, Medicaid, and other vulnerable patients.” 4 Safety-net hospitals have been associated with reduced adherence to quality-of-care measures and a lower use of curative-intent surgery in patients with NSCLC.…”
mentioning
confidence: 99%